Assessment of micropollutant degradation using multi-element compound-specific isotope analysis - (:unkn) unknown (My University, 2025)
The frequent detection of polar organic micropollutants such as pesticides, consumer care products or pharmaceutical in water is an increasing concern for human and ecosystem health. Currently, little is known about the long-term fate of such compounds in aquatic systems due to the difficulty in demonstrating their degradation. Compound-specific isotope analysis (CSIA) of multiple elements is a potentially powerful method to evaluate organic micropollutant transformation because pathway-specific isotope fractionation is expected to occur for many compounds as suggested by some recent studies of the applicants. For classical priority pollutants such as chlorinated and petroleum hydrocarbons, CSIA has become a well-established method to identify and quantify degradation pathways. The extension of the CSIA approach to micropollutants is challenging for several reasons: Micropollutants are typically present in lower concentrations thus requiring more extensive preconcentration, they often are more polar hence requiring derivatization before gas chromatographic analysis, they frequently include heteroatoms complicating their conversion to measurement gases for mass spectrometry, and they are degraded by a wide range of mechanisms, whose isotope effects are not known yet. The main goal of this project is to extend the CSIA approach for assessing degradation pathways to polar organic micropollutants, thereby demonstrating that (i) it is feasible to analyze the isotopic composition of common organic micropollutants at field-relevant concentration levels (analytical method development), (ii) a multi-isotope approach can be used to gain unique insight into pathways of micropollutant degradation (process studies), (iii) transformation processes can be identified and quantified based on micropollutants' isotope ratios under field conditions and/or in experimental settings mimicking field conditions (system studies). Given the numerous challenges that have to be overcome to establish multi-element CSIA for micropollutant, a collaborative research strategy will be chosen that brings together leading experts in the field of CSIA and micropollutant studies from the University of Neuchâtel (UNINE), the Helmholtz Zentrum München (HGMU), the Swiss Federal Institute of Aquatic Science and Technology (Eawag), and Agroscope Reckenholz-Tänikon Research Station (ART). The participation of the German partner, HGMU, is essential for the analytical part of the project and will make it possible to transfer some of its unique expertise in micropollutant CSIA to Swiss institutions. The project consists of three PhD theses. Each of them focuses on a specific, highly-relevant organic micropollutant and emphasizes one of the three conceptual activities, that is analytical methods, transformation processes, and system studies. Subproject 1 (led by UNINE) investigates if multi-element CSIA can be used to identify and quantify micropollutant transformation in complex systems where transformation and transport processes interact. The project will make use of lysimeter experiments, which allow control of experimental conditions. The project will focus on substances for which pathway-specific isotope fractionation and analytical methods are already established. Subproject 2 (HGMU) is dedicated to the challenge of multielement isotope analysis for micropollutants. Its objectives are the isotope analysis of lysimeter samples, as well as the analytical method development and degradation process studies for chloridazon and desphenyl-chloridazon as emerging pesticides of concern. Subproject 3 (Eawag) targets a class of consumer chemicals (benzotriazoles), which are widely encountered in the aquatic environment but whose fate assessment is hampered by the lack of knowledge regarding (bio)degradation processes. The overall project includes extensive collaboration across subprojects: Multi-element-CSIA methods will be jointly developed bringing together the complementary expertise of the partners, laboratory process studies will be carried out in close collaboration sharing experimental setups and tools, and the lysimeter experiments will be jointly executed sharing the high load of concentration measurements and CSIA analysis. In order to favor collaboration, joint semi-annual meetings are planned, as well as short term scientific visits of the PhD fellows at the partner institutions. The project is expected to lead to a series of groundbreaking publications on multi-element micropollutant CSIA and bring the method a substantial step forward towards its field application as unique method to characterize the long-term micropollutant fate in aquatic systems, a pressing issue for society.
Keywords: biodegradation; stable isotopes; organic micropollutants